In Vitro Fluoride-Release/Recharge Pattern and_x000D_ Antimicrobial Effects of Current Restorative_x000D_ Materials Used in Pediatric Dentistry - YARAT, AYŞEN; TACAL ASLAN, BESTE; AKYÜZ, SERAP HATİCE; KADİR, TANJU (My University, 2020)
Objective: The aim of this in vitro study was to investigate the fluoride-releasing/recharging and antimicrobial effects of restorative materialsused in pediatric dentistry.Material and Method: High-viscosity and resin-modified glass-ionomercement, glass carbomer, compomer, giomer and composite weretested. Dental materials’ fluoride-release was measured in distilled water(DW) and artificial saliva (AS) for eight weeks using a fluoride-specificelectrode. At the end of eight weeks, specimens were divided intothree groups for recharging with acidulated phosphate fluoride gel andfluoride varnish. After recharge, fluoride release was measured again.Agar diffusion test was used to assess antimicrobial effects againstS. mutans and L. acidophilus. The statistical analysis was done withMann-Whitney U and Friedman tests using SPSS-22 software.Results: High-viscosity glass-ionomer cement showed the highestfluoride-release in both storage media, followed by glass carbomer,while giomer demonstrated the lowest. After recharge, the increasein the varnish group was significantly higher than others (p<0.05).Fluoride-release in DW groups was significantly higher than in the ASgroups for all materials during the test period (p<0.05). None of thematerials showed antimicrobial effects.Conclusion: It was concluded that fluoride-release from glass ionomer-based materials is higher than that from resin-based materials.Fluoride-release from materials decreases in AS. Glass carbomer can beused as an alternative to glass ionomers.

Amaç: İn vitro çalışmamızın amacı çocuk diş hekimliğinde kullanılan_x000D_ güncel restoratif materyallerin fluorid salınımını saptamak, yeniden_x000D_ yükleme sonrası salınımlarını değerlendirmek ve bu materyallerin antimikrobiyal_x000D_ etkinliğini araştırmaktır._x000D_ Gereç ve Yöntem: Çalışmamızda yüksek viskoziteli cam iyonomer siman,_x000D_ rezin modifiye cam iyonomer siman, cam karbomer, kompomer, giomer_x000D_ ve rezin kompozit kullanıldı. Fluorid salınımı distile su (DS) ve yapay tükürük_x000D_ (YT) içerisinde 8 hafta boyunca fluorid spesifik elektrod ile ölçüldü._x000D_ 8. haftanın sonunda örnekler üç gruba ayrıldı. Birinci gruba hiçbir ajan_x000D_ uygulanmazken, ikinci gruba asidüle fosfat fluorid jel, üçüncü gruba ise_x000D_ fluorid verniği uygulandı ve yükleme sonrası salınımları incelendi. S. mutans_x000D_ and L. acidophilus’a karşı antimikrobiyal etkinin değerlendirilmesinde_x000D_ agar difüzyon testi kullanıldı. İstatistiksel analizler SPSS-22 programı_x000D_ kullanılarak Mann-Whitney U ve Friedman testleri ile yapıldı._x000D_ Bulgular: Her iki ortamda da en yüksek fluorid salınımını yüksek viskoziteli_x000D_ cam iyonomer siman yaparken, bunu cam karbomer izledi. En düşük_x000D_ salınım giomerde saptandı. Fluorid yüklemesi sonrası tüm materyallerin_x000D_ salınımı artarken; vernik gruplarındaki artış, diğer gruplardan anlamlı_x000D_ düzeyde yüksek bulundu (p<0,05). Çalışma boyunca materyallerin DS_x000D_ gruplarındaki fluorid salınımı YT gruplarından anlamlı derecede yüksek_x000D_ bulundu (p<0,05). Materyallerin hiçbiri antimikrobiyal etki oluşturmadı._x000D_ Sonuç: Cam iyonomer esaslı materyallerden fluorid salınımının daha_x000D_ çok olduğu; yapay tükürük içerisinde materyallerin salınımının azaldığı_x000D_ ve cam karbomerin fluorid salınımı açısından cam iyonomer simanlara_x000D_ alternatif olarak kullanılabileceği görüldü.
Çocuk Diş Hekimliğinde Kullanılan Güncel Restoratif Materyallerden Fluorid Salınımı, Yeniden Yüklenmesi ve Antimikrobiyal Etkilerinin İn Vitro Olarak İncelenmesi